It Takes Two to Tango: The Management of Academic–Industry Partnerships Requires Multiple Perspectives. Issue 4 (December 2018) - Maynard, M. Travis; Conroy, Samantha; Lacerenza, Christina N.
Abstract : Field-based research allows the domain of organizational research to remain true to its applied roots and conduct research on topics that are timely and relevant within actual organizations. However, anyone who has conducted field research knows that conducting such work is challenging and can be viewed as more of a dance between the scholar and the practitioner, requiring well-timed and coordinated moves. As Lapierre et al. (2018 ) allude to in the focal article, such projects can turn into a balancing act for researchers as they attempt to conduct publishable research with robust practices and designs while also appeasing the needs and expectations of organizational members and leaders.